Contextual leadership practices - Noman, Mohammad; Awang Hashim, Rosna; Shaik Abdullah, Sarimah (SAGE Publications, 2016)
The study of context-based leadership practices has gained currency during the last decade.This study aims to complement the recent efforts of researchers in identifying the context-based leadership practices of successful school leaders, and deliberating how these practices are enacted within their own unique contexts.An in-depth case study was conducted in a successful school in northern Malaysia using a combination of case study methods and grounded theory. Case study methods were used for data collection from multiple sources, employing a semi-structured interview protocol derived from the one used in several studies conducted under the International Successful School Principal ship Project.The findings of the case study reveal that strong interpersonal skills, people-centered leadership, clear communication of vision and goal, focus on academic achievement, co-curricular activities, developing people and creating a positive work environment are all vital constituents of successful leadership.The findings will attempt to add to the scant literature on context-based leadership practices from Malaysia.Implications for practice can be drawn for policymakers, who must resist over-reliance on borrowed leadership models, while practitioners need to prioritize their practices based upon the contextual requirements to succeed.